KONTRIBUSI DAYA LEDAK OTOT LENGAN DAN KOORDINASI MATA-TANGAN TERHADAP KETEPATAN SERVIS ATAS PEMAIN BOLA VOLI SMAN 1 TELUK NISAP KECAMATAN KUBU BABUSSALAM - Maria Lestari; Saripin '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is not optimal yet accuracy overhead servicing volleyball players SMAN 1 Teluk Nisap. This problem can be seen from the observation of researchers during a match or training. This is presumably because of the explosive power arm muscles and hand-eye coordination. Therefore, the purpose of this study was to determine whether there is a contribution explosive power arm muscles and hand-eye coordination to the overhead serve accuracy on volleyball players at SMAN 1 Teluk Nisap. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As independent variables (X1) is explosive power arm muscles, (X2) is hand-eye coordination while the dependent variable (Y) is the overhead serve accuracy on volleyball. This research data obtained from the two hand medicine ball put test, catching throwing at the wall test andaccuracy serve test above. Based on the results of research it can be concluded as : the results obtained explosive power arms muscles had significant relationship with the overhead serve accuracy on volleyball players at SMA Negeri 1 bay Nilap Babussalam Kubu district, characterized by results obtained by the rhitung 0.46> rtabel 0.444, with a contribution of 21%. From the results obtained hand-eye coordination significant relationship to the overhead serve accuracy on volleyball players at SMA Negeri 1 Teluk Nilap Babussalam Kubu district, characterized by the results obtained by the rhitung 0.50> rtabel 0.444, with a contribution of 25%. There is a significant relationship together between the explosive power arm muscles and hand-eye coordination to the overhead service accuracy on volleyball players at SMA Negeri 1 Teluk Nilap Babussalam Kubu district, is characterized by the results obtained rhitung 0.55> rtabel 0.444, with a contribution of 30 %.Keywords : Explosive Power, Arms Muscles, Coordination, Hand-Eye, Serve